2018
DOI: 10.5812/aapm.81077
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect and Hemodynamic Changes Due to Dexmedetomidine Versus Fentanyl During Elective Colonoscopy: A Double-Blind Randomized Clinical Trial

Abstract: BackgroundThere are different methods used for anesthesia during a colonoscopy procedure.ObjectivesThe aim of this study was to compare the analgesic effect and hemodynamic changes due to dexmedetomidine and fentanyl during elective colonoscopy.MethodsThis double-blind clinical trial was conducted on 80 patients aged 20 - 70 years, candidates for elective colonoscopy, who were randomly divided into two equal groups. In the intervention group (group D), dexmedetomidine 1 mcg/kg was given 10 minutes before start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 17 publications
(22 reference statements)
3
30
0
Order By: Relevance
“…Several pharmacological agents are developed to control hypotension, including remifentanil (3), magnesium sulphate (4), nitroglycerine (5), esmolol (5), and dexmedetomidine (5). The effect of dexmedetomidine on controlling hypotension is well known and is compared with other agents like remifentanil (3), magnesium sulphate (4), esmolol (5), clonidine (6), and fentanyl (7,8). Our institute has a history of providing FESS to normotensive patients under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several pharmacological agents are developed to control hypotension, including remifentanil (3), magnesium sulphate (4), nitroglycerine (5), esmolol (5), and dexmedetomidine (5). The effect of dexmedetomidine on controlling hypotension is well known and is compared with other agents like remifentanil (3), magnesium sulphate (4), esmolol (5), clonidine (6), and fentanyl (7,8). Our institute has a history of providing FESS to normotensive patients under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Although several clinical studies reported that dexmedetomidine can decrease hemodynamic responses and is associated with improved quality of surgical procedures of FESS, but we could not find a study on comparing dexmedetomidine with labetalol during FESS. Hence, we decided to perform such a comparison in our institute (3,7).…”
Section: Introductionmentioning
confidence: 99%
“…8 Unfortunately, intravenous infusion of dexmedetomidine may be accompanied by hypertension and bradycardia, which will endanger patient safety. 9,10 The problem of hypoxemia induced by propofol sedation has received more attention recently, but a general agreement in clinical practice is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…found that the intensity of pain was less in patients doing colonoscopy receiving dexmedetomidine than in other patients who received fentanyl. Dexmedetomidine resulted in a lower dose of rescue propofol when compared to the fentanyl group (17).…”
Section: Discussionmentioning
confidence: 83%